Heat of Formation of Titanium Trichloride - Johnson, Walter H. (J Res Natl Bur Stand A Phys Chem, 1960)
A calorimetric comparison of the heat of hydrolysis of TiCl(4)(liq) with the heat of oxidation and hydrolysis of TiCl(3)(c) has been made. The following value is reported for the combination of these data according to the process: [Formula: see text] A combination of this value with −192.3 ±0.7 kcal/mole for the heat of formation of TiCl(4)(liq) and with the standard heats of formation of HCl(g) and HI(g) gives for TiCl(3)(c), ΔHf°(25 °C) = −172.4±0.8 kcal/mole.